modular function produced via infinite product of weight-k modular forms

Suppose I have a modular form f_{k}(z) of weight k:

f_{k}\left(\frac{az+b}{cz+d}\right) = (cz+d)^{k} f_{k}(z)

Then consider the following infinite product:

u(z) = \prod_{n=1}^{\infty} \frac{f_{4n-3}(z)f_{4n}(z)}{f_{4n-2}(z)f_{4n-1}(z)}

Ignoring convergence problems for the moment, formally u(z) must be a modular function, since:

\prod_{n=1}^{\infty} \frac{f_{4n-3}(z)f_{4n}(z)}{f_{4n-2}(z)f_{4n-1}(z)} = \prod_{n=1}^{\infty} \frac{(cz+d)^{4n-3}f_{4n-3}(z)(cz+d)^{4n}f_{4n}(z)}{(cz+d)^{4n-2}f_{4n-2}(z)(cz+d)^{4n-1}f_{4n-1}(z)} = \prod_{n=1}^{\infty} \frac{f_{4n-3}\left(\frac{az+b}{cz+d}\right)f_{4n}\left(\frac{az+b}{cz+d}\right)}{f_{4n-2}\left(\frac{az+b}{cz+d}\right)f_{4n-1}\left(\frac{az+b}{cz+d}\right)}

And
\frac{(cz+d)^{4n-3}(cz+d)^{4n}}{(cz+d)^{4n-2}(cz+d)^{4n-1}} = (cz+d)^{4n-3+4n-4n+2-4n+1)} = (cz+d)^{0} =1

Advertisements

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s